PENGARUH PENERAPAN MODEL PEMBELAJARAN LANGSUNG BERBANTUAN MEDIA FLIPCHART TERHADAP HASIL BELAJAR TEKNIK TUMPANG TINDIH PADA ALAS PANAS SISWA KELAS XI SMK NEGERI 1 BERASTAGI - Hutapea, Flora; Ginting, Elfrida (Universitas Negeri Medan, 2017)
ABSTRACT The research aims to know: 1) To know the results of learning overlap technique on the base of heat by using conventional learning model of students of class XI SMK Negeri 1 Berastagi. 2) To know the result of learning technique of overlap on the base of heat after using direct instruction model assisted by flipchart media of student of class XI SMK Negeri 1 Berastagi. 3) To know how far the influence of learning result of overlap technique on the base of heat after using direct instruction model assisted by flipchart media in class XI SMK Negeri 1 Berastagi. The population in this study are 97 students of class XI Kriya Tekstil SMK Negeri 1 Berastagi. Sampling technique using purposive sample that is sampling technique with certain considerations. The sample in this research is 64 students consisting of experiment class of 3 students and control class of 32 students, using quasi experiment method (Quasi experiment). The results of this research indicate that the level of trends in the results of learning overlap technique on the heat base of the class XI Kriya Tekstil SMK Negeri 1 Berastagi for experimental class tend to be very high at 75%. And the tendency level of overlap technique learning result for the control class tends to be high but only 46,87%. To test the data normality using the Liliefors formula at a significant level of 0.05 with dk = 32, in obtaining the results of learning data overlap technique on the heat base of experimental class is normally distributebecause Lcount<Ltable (0.051592 <0.156) and control class with dk = 32, is normally distributed because Lcount<Ltable (0,018296 <0,156). Homogeneity test, obtained Fcount <Ftabel is 0,45 <1,83 so that both research class have the same variance (homogeneous). The result of hypothesis test by using t-test in obtaining tcount of 4,261 and ttable at significant level 0,05 with dk = 62 equal to 1,671. Thus tcount>ttable (4,261> 1,671). Therefore it can be concluded that there is an effect of the application of direct learning model assisted by flipchart media on the results of learning overlap technique on the heat base of students of class XI SMK Negeri 1 Berastagi. Based on the results of the calculation above, it can be seen that the application of direct learning model assisted by flipchart media is well used in SMK Negeri 1 Berastagi, especially in the sewing lesson. Kata Kunci: Model Pembelajaran Langsung berbantuan Media Flipchart, Teknik Tumpang Tindih